Assessing the Impact of Technological Factors on the Stability of Liposomes the Photosensitizer Phthalocyanine Series - T. A. Timofeeva; M. V. Dmitrieva; L. L. Nikolaeva; O. L. Orlova; N. A. Oborotova; A. P. Polozkova; I. I. Krasnyuk (Разработка и регистрация лекарственных средств, 2019)
Introduction. Liposomal technologies are widely used in medicine and cosmetology as a delivery system for diagnostic and medicinal products and biologically active substances. The undoubted practical importance at the stage of development of a liposomal preparation is represented by the characteristic and assessment of the sustainability of the obtained product, and special attention is paid to the study of the latter. Essentially, the methods for their preparation affect the stability of liposomes; therefore, the study of the influence of technological factors on the properties of the product at various stages of the preparation of liposomes is very important. This article is devoted to the study of the dependence of the quality of liposomes loaded with a phthalocyanine photosensitizer – thiosens, on the conditions of their production.Aim. Detection of the influence of various technological factors on the stability indicators of the liposomal form of the thiosens photosensitizer.Materials and methods. For this purpose, an analysis of the average size, polydispersity and zeta (ζ) potential of the liposomes of thiosens obtained at the stage of hydration of the lipid film, filtration of the liposomal dispersion, its extrusion, homogenization, ultrasonic treatment, and lyophilization was carried out.Results and discussion. During the preparation of a liposomal preparation, various changes in conditions can be made within the framework of the technological process. At each stage of obtaining a liposomal form, there are many critical points and parameters that must be strictly monitored and controlled. In the course of the work, the influence of technological factors on the stability of liposomal intermediate and finished products was assessed. The conditions of the most effective hydration with the formation of a stable dispersion of multilayer liposomes of thiosens and the optimal method of their grinding have been determined. It was also shown that liposomes formed after rehydration of the lyophilisate are more uniform in size and have the highest ζ-potential value in comparison with non-lyophilized liposomal dispersion.Conclusion. Using the example of a thiosens phthalocyanine photosensitizer liposomes, the influence of various technological factors on the stability of this nanostructure is shown, therefore, the characteristic and assessment of the sustainability of the resulting product according to 3 main indicators – vesicle size, polydispersity index, and ζ-potential are of undoubted practical importance.